Pengaruh Pupuk Hayati Berbasis Hidrogel dan Pupuk P terhadap Pertumbuhan dan Hasil Jagung pada Inceptisols asal Jatinangor - Betty Natalie Fitriatin; Nabila Syifa Ariani; Haryo Probo Kusumo; Mieke Rochimi Setiawati (Soilrens, 2022)
Inceptisols are soils that have problems with fertility. Inorganic P fertilizer is a quick choice to restore nutrient availability for plants, but long-term use may harm soil and plants. Another alternative to this problem by using a biofertilizer. Biofertilizer contains microbes that can promote plant growth by increasing the supply of nutrients through their biological activities in the soil. Some microbes are known to have to dissolve phosphate ability through secretion of organic acids and enzymes mechanism. This experiment was conducted to examine the effect of hydrogel-based biofertilizer combined with inorganic P fertilizer (SP-36) on the growth and maize yields on Inceptisols Jatinangor. The biofertilizers were a consortium of phosphate solubilizing microbes (PSM) consisting of Bacillus subtilis, Pseudomonas mallei, Burkholderia cepacia, and Trichoderma asperellum. The pot experiment using a Randomized Block Design (RBD) consisted of 9 treatments with 3 replications. The treatments consisted of control, recommended dose of inorganic P fertilizer (100 kg Ha-1), biofertilizer dose of 50 kg Ha-1, and a combination of biofertilizer and inorganic P fertilizer. The results showed that the combination of ½ dose of hydrogel-based biofertilizer and ¾ dose of P fertilizer increased maize yield. In addition, the application of biofertilizer can reduce inorganic P fertilizer needs up to ¾ recommended dose.